Digital Technology-Based Education Transformation in The Capital of The Archipelago - Amrizal, Amrizal; Setiawan, Andi; Wijayanti, Dian; Setiadi, Alpian; Rukma, Andi Satriani Nanda; Hikma, Muqtaridatul (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2026)
The rapid advancement of digital technology has significantly transformed various sectors, including education, requiring adaptive and innovative approaches to learning systems. This study aims to analyze the transformation of digital technology-based education in the Indonesian Capital City (IKN) and to examine the readiness of the community to adapt to such transformation. Using a qualitative approach with a literature review method, this research synthesizes findings from relevant academic sources, policy documents, and previous studies related to digital education, smart city development, and human resource readiness. The results indicate that the transformation of education in IKN is closely linked to the integration of digital infrastructure, such as e-learning platforms and hybrid learning systems, which enhance accessibility, flexibility, and learning effectiveness. Furthermore, the implementation of digital education supports the broader vision of IKN as a smart city by fostering a digitally literate and innovation-oriented society. However, several challenges remain, including unequal access to digital infrastructure, varying levels of digital literacy, and limited institutional readiness. These challenges highlight the importance of comprehensive strategies that integrate technological development with human resource capacity building. The study also finds that community readiness plays a crucial role in determining the success of digital education transformation, as it influences the adoption and sustainability of technology-based learning. Therefore, the government and educational institutions must prioritize digital literacy programs, infrastructure development, and inclusive policies to ensure equitable access to education. This research contributes to the existing literature by providing a comprehensive analysis of digital education transformation within the context of a newly developed capital city and offers practical implications for policymakers and stakeholders in designing sustainable and inclusive education systems in the digital era